Evaluation of the potential accuracy of the pulsed radio signals source coordinate determination by the positioning system using a single uav-sensor - Baldytchev, M.T.; Laptev, I.V.; Chebotar, I.V.; Gaychuk, Y.N.; Pivkin, I.G.; Timoshenko, A.V.; Galtseva, O.V. (KU publ., 2020)
An approach to determining the coordinates of pulsed radio signals sources by the positioning system in the application of a single unmanned aerial vehicles sensor is shown in this article. The range-difference location method allows to determinate an informative coordinate parameter without retransmission and internal synchronization of receiving points. The result is achieved by improving the well-known scientific and methodological apparatus with considering some features of the operation mode of pulsed radio signals sources. Presenting results of the simulation allow to estimate the influence of main input factors on the potential accuracy of the pulsed radio signal source coordinate determination
Ұшқышсыз ұшу аппаратының бір сенсорын қолдануымен жайғастыру жүйесімен импульстік радиодабылдар көзінің координаттарын анықтаудың потенциалды дәлдігін бағалау
Оценка потенциальной точности определения координат источника импульсных радиосигналов системой позиционирования с использованием одного датчика беспилотного летательного аппарата
Keywords: coordinate-informative parameter; unmanned aerial vehicles sensor; pulsed radio signals sources; the range-difference location method